2019
DOI: 10.1093/asj/sjz028
|View full text |Cite
|
Sign up to set email alerts
|

Anatomical Map of the Facial Artery for Facial Reconstruction and Aesthetic Procedures

Abstract: Background The facial artery (FA) is the main blood vessel supplying the anterior face and an understanding of its anatomy is crucial in facial reconstruction and aesthetic procedures. Objectives The aim of this study was to assess the many anatomical features of the FA utilizing a multidimensional approach. Methods Head and neck computed tomographic angiogra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
37
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 36 publications
(38 citation statements)
references
References 38 publications
1
37
0
Order By: Relevance
“…Characteristics of each study that fulfilled all criteria for inclusion are shown in Table 1. Out of 24 studies, 20 were based on cadaver dissections regarding a total of 1274 arteries in 745 cadavers (Dickson et al, 2014; Dupoirieux et al, 1999; Gardetto et al, 2002; Gocmen‐Mas et al, 2015; Koh et al, 2003; Laurentjoye et al, 2012; Lee, Gil, et al, 2015; Lee, Yang, et al, 2015; Lohn et al, 2011; Loukas et al, 2006; Midy et al, 1986; Mitz et al, 1973; Nakajima et al, 2002; Niemann et al, 2019; Niranjan, 1988; Pilsl et al, 2016; Pinar et al, 2005; Qassemyar et al, 2012; Saban et al, 2012; Tansatit et al, 2021), three on computed tomography angiography (CTA) images of a total of 726 arteries gathered from 423 patients (Furukawa et al, 2013; Hong et al, 2020; Koziej et al, 2019) and one included 119 arterial patterns gathered from 110 human fetuses (Kozielec & Józwa, 1977). In total, morphological data of 2119 arteries were included in this meta‐analysis.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Characteristics of each study that fulfilled all criteria for inclusion are shown in Table 1. Out of 24 studies, 20 were based on cadaver dissections regarding a total of 1274 arteries in 745 cadavers (Dickson et al, 2014; Dupoirieux et al, 1999; Gardetto et al, 2002; Gocmen‐Mas et al, 2015; Koh et al, 2003; Laurentjoye et al, 2012; Lee, Gil, et al, 2015; Lee, Yang, et al, 2015; Lohn et al, 2011; Loukas et al, 2006; Midy et al, 1986; Mitz et al, 1973; Nakajima et al, 2002; Niemann et al, 2019; Niranjan, 1988; Pilsl et al, 2016; Pinar et al, 2005; Qassemyar et al, 2012; Saban et al, 2012; Tansatit et al, 2021), three on computed tomography angiography (CTA) images of a total of 726 arteries gathered from 423 patients (Furukawa et al, 2013; Hong et al, 2020; Koziej et al, 2019) and one included 119 arterial patterns gathered from 110 human fetuses (Kozielec & Józwa, 1977). In total, morphological data of 2119 arteries were included in this meta‐analysis.…”
Section: Resultsmentioning
confidence: 99%
“…As a solution, the authors decided to assemble the extracted termination patterns of FA in an apportionment that included all data. For this purpose, the compilation method presented by Furukawa et al (2013) with later modification by Koziej et al (2019) as shown in Figure 2 was used. In this compilation method, the FA termination patterns were divided into five types: (1) Type 1 is a short FA course, in which it terminates proximally to the superior labial artery as the superior or inferior labial artery; (2) In type 2, the FA terminates distally to the superior labial artery near the nasolabial fold as an inferior alar artery; (3) In type 3, the FA extends to the lateral nasal or angular branch and runs in the alar‐facial crease; (4) In type 4, the FA forms a duplex with the dominant lateral angular branch and traverses the supra‐alar crease, which is its anatomical landmark; and (5) In type 5, FA is hypoplastic and the remaining course is supplied by the dominant transverse facial artery (Furukawa et al, 2013; Koziej et al, 2019).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Preoperative knowledge on individual anatomical variations in facial artery patterns may aid maxillofacial surgeons in reconstructive planning to effectively manage facial injuries with arterial involvement, dermatologists in aesthetic procedures, and radiological anatomy professionals in the field of malignancies for the treatment of various facial tumors by embolization [13][14][15][16]. Information on variations in the facial artery may also contribute to damage risk mitigation during cosmetic procedures such as neurotoxin or filler injections [17,18].…”
Section: Introductionmentioning
confidence: 99%
“…To improve clinical outcomes, we further recommend consulting modern anatomical research. For instance, a recent anatomical study by Koziej et al revealed the presence of multiple variants of facial artery relations to the nasolabial fold [2]. In the most common variant, the facial artery is located medially to the nasolabial fold.…”
mentioning
confidence: 99%